Tindak Tutur Ilokusi Asertif dalam Film Kartun Atho Ibnu Abi Rabah dalam Channel Youtube Sukardi Hasanudin - Hafidz, Gamal Zulham; Huda, Ismuaji Nur; Ulhaq, Jia; Budiman, Muhammad Farhan; Rosyadi, Muhammad Yesha Zula (Jurusan Bahasa dan Sastra Arab Fakultas Adab dan Humaniora UIN Imam Bonjol Padang, 2023)
The object of this research is in the form of speech acts contained in the cartoon film Atho Ibnu Abi Rabah in Sukardi Hasanudin's Youtube Channel. And this research aims to describe and explain the assertive illocutionary speech acts in the cartoon movie Atho Ibnu Abi Rabah. This type of research is qualitative-descriptive. The data collection method uses the method of listening and recording. Initially, the researchers listened repeatedly to the utterances contained in the animated film. Then record the speech data found and classify according to the problem formulation. Furthermore, the data was analyzed. The result of this research is found 13 data with the description of 5 assertive data in the form of stating, 2 assertive data in the form of suggesting, 5 assertive data in the form of telling, and 1 assertive data expressing an opinion.